2021
DOI: 10.1097/eja.0000000000001450
|View full text |Cite
|
Sign up to set email alerts
|

Acute pain after serratus anterior plane or thoracic paravertebral blocks for video-assisted thoracoscopic surgery

Abstract: BACKGROUND Serratus anterior plane blocks (SAPBs) and thoracic paravertebral blocks (TPVBs) can both be used for video-assisted thoracic surgery. However, it remains unknown whether the analgesic efficacy of a SAPB is comparable to that of a TPVB. OBJECTIVE We tested the primary hypothesis that SAPBs provide noninferior analgesia compared with TPVBs for video-assisted thoracic surgery. DESIGN A noninferiorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 26 publications
2
32
0
Order By: Relevance
“… 36–38 It has been reported that regional techniques combined with general anaesthesia provide better perioperative analgesia by completing the somatosensorial and sympathetic block and have an opioid analgesic sparing effect. 39 The results of our study suggest that the average NRS score within 48 h postoperatively in group TG was significantly lower than that in group GA ( P <0.05), which is consistent with the results of Qiu et al 40 who found that TPVB provided analgesia that was superior to general anaesthesia alone during the initial 2 h after VATS in a noninferiority randomized trial. Our results are also similar to those from a study by Chu et al 6 who demonstrated that TPVB could provide statistically better pain relief in VATS lobectomy in a randomized clinical trial.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“… 36–38 It has been reported that regional techniques combined with general anaesthesia provide better perioperative analgesia by completing the somatosensorial and sympathetic block and have an opioid analgesic sparing effect. 39 The results of our study suggest that the average NRS score within 48 h postoperatively in group TG was significantly lower than that in group GA ( P <0.05), which is consistent with the results of Qiu et al 40 who found that TPVB provided analgesia that was superior to general anaesthesia alone during the initial 2 h after VATS in a noninferiority randomized trial. Our results are also similar to those from a study by Chu et al 6 who demonstrated that TPVB could provide statistically better pain relief in VATS lobectomy in a randomized clinical trial.…”
Section: Discussionsupporting
confidence: 91%
“…The dosage of intraoperative and postoperative sufentanil in group TG was significantly lower than in group GA ( P <0.01). This indicated that TPVB could significantly reduce perioperative pain, which was consistent with the results of Qiu et al 40 who found that PTVB reduced the use of sufentanil during surgery by about 30%, and that patients required smaller amounts of rescue drugs within 24 h after operation. Zhang et al 43 demonstrated that the reduced consumption of remifentanil occurred in response to TPVB in patients undergoing pulmonary surgery in a randomized trial.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, a small randomized trial failed to find any difference in pain scores or opioid consumption in patients who receive either SAPB or ICNB for VATS (124). Interestingly, a recent randomized non-inferiority trial of SAPB and PVB for VATS showed no significant difference in post-operative pain scores at two hour between the two approaches, but also no difference in pain scores for either compared to no block at 24 or 48 hours, and no difference in 24 hours post-operative opioid consumption (125).…”
Section: Sapb For Vatsmentioning
confidence: 99%
“…TPVB is a unilateral block technique; therefore, contralateral respiratory and sympathetic functions can be preserved. This function may be associated with reduced PPCs, postoperative bleeding, and urinary retention [51]. The complications of TPVB are similar to those of TEA; however, spinal cordrelated complications are more likely to occur after TEA, whereas pulmonary complications are more common after TPVB [52].…”
Section: Tpvb Vs Sapbmentioning
confidence: 99%